Electrochromic Properties of Graphene Doped TiO2 Layer Deposited by Thermionic Vacuum Arc. (24th July 2020) - Pat, Suat; Akkurt, Nihan; Mohammadigharehbagh, Reza; Olkun, Ali; Demirkol, Uğur; Özgür, Mustafa; Korkmaz, Şadan
Abstract : Electrochromic (EC) device has been widely used many applications and TiO2 is a popular electrode material. Graphene doping affects Li + ion intercalation/deintercalation mechanism in positive way for energy storage devices. So high performance devices can be manufactured by doping graphene. In this study, graphene doped TiO2 layers have been deposited by thermionic vacuum arc system. According to AFM results, mean height of the grains for the graphene doped TiO2 layer deposited onto fluorine tin oxide (FTO) and indium tin oxide (ITO) coated glass substrates were measured 10 nm and 100 nm, respectively. Anatase TiO2 and graphene bands were determined in Raman analyses. Refractive index of graphene doped TiO2 layer was found approximately 1.80 @ 550 nm. Optical modulation values for the FTO and ITO coated glass substrates were calculated as 25% and 11% @ 420 nm, respectively. Coloration efficiencies were obtained as 28 and 77 cm 2 /C for the graphene doped TiO2 layers deposited onto FTO and ITO coated glass substrates, respectively. Maximum transparency value was 85% in optical region. According to the coloration efficiency, it found that graphene dopant is proper and promising two dimensional material to improve TiO2 performance in EC device application.